Correlation between Circulating Levels of Pro-Inflammatory Cytokines TNF-alpha and Vascular Calcification Inhibitor Matrix Gla Protein in Obese Men - Trilis Yulianti; Mansyur Arif; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Adult obesity is rapidly increasing in the world including Indonesia. Tumor necrosis factor α (TNF-α) was chronically elevated in obese adipose tissue. TNF-α, a pleiotropic cytokine and also a regulator of bone formation, may might represent an important link between obesity and vascular calcification. Elegant genetic studies in mice and human have highlighted the important roles for Matrix Gla Protein (MGP) as an inhibitor of vascular calcification. The aim of this study was to examine the correlation between circulating levels of pro-inflammatory cytokines TNF-α and vascular calcification inhibitor MGP in obese men.METHODS: This was an observational cross-sectional study including 40 central obese men (waist circumference ≥90 cm) aged 31-60 years old. Serum MGP and serum TNF-α concentrations were quantified by ELISA principle. Fasting plasma glucose was assessed using hexokinase methods, triglyceride by GPO-PAP methods, and creatinine by Jaffe methods. All assays were performed according to the manufacture instruction. Statistical analysis was performed with SPSS for windows ver 16. Univariate analysis were performed to analyze mean, maximum, minimum value and SD. Pearson correlation statistic were performed to determine the correlation between variables. Significance value were define as alpha level = 0.05 based on two-tailed tests.RESULTS: The cross-sectional study (n=40) showed that the advancing age was correlated with plasma TNF-α concentration (r=0.348; p=0.028). The mean concentration of TNF-α and MGP were 8.323 and 8.368, respectively. We found a significant negative correlation between TNF-α with MGP (r=-0.425; p=0.006) and a significant correlation between TNF-α and triglyceride (r=0.375; p=0.017).CONCLUSIONS: Circulating level of TNF-α was inversely correlated with MGP concentration in obese men. This finding suggested that high level TNF-α leads to low MGP concentration obese men, hence, limits inhibitory capacity in vascular calcification.KEYWORDS: hypertension, obesity, vascular calcification, MGP, TNF-α